Leptomeningeal Cells Transduce Peripheral Macrophages Inflammatory Signal to Microglia in Reponse to Porphyromonas gingivalis LPS - Yicong Liu; Zhou Wu; Xinwen Zhang; Junjun Ni; Weixian Yu; Yanmin Zhou; Hiroshi Nakanishi (Mediators of Inflammation)
We report here that the leptomeningeal cells transduce inflammatory signals from peripheral macrophages to brain-resident microglia in response to Porphyromonas gingivalis (P.g.) LPS. The expression of Toll-like receptor 2 (TLR2), TLR4, TNF-α, and inducible NO synthase was mainly detected in the gingival macrophages of chronic periodontitis patients. In in vitro studies, P.g. LPS induced the secretion of TNF-α and IL-1β from THP-1 human monocyte-like cell line and RAW264.7 mouse macrophages. Surprisingly, the mean mRNA levels of TNF-α and IL-1β in leptomeningeal cells after treatment with the conditioned medium from P.g. LPS-stimulated RAW264.7 macrophages were significantly higher than those after treatment with P.g. LPS alone. Furthermore, the mean mRNA levels of TNF-α and IL-1β in microglia after treatment with the conditioned medium from P.g. LPS-stimulated leptomeningeal cells were significantly higher than those after P.g. LPS alone. These observations suggest that leptomeninges serve as an important route for transducing inflammatory signals from macrophages to microglia by secretion of proinflammatory mediators during chronic periodontitis. Moreover, propolis significantly reduced the P.g. LPS-induced TNF-α and IL-1 β production by leptomeningeal cells through inhibiting the nuclear factor-κB signaling pathway. Together with the inhibitory effect on microglial activation, propolis may be beneficial in preventing neuroinflammation during chronic periodontitis.